(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The present article presents a methodological-theoretical proposal to understand communication in the psycho-therapeutic process, more specifically in the Cognitive-Behavioral Therapies (CBT). The latest advancements of the CBTs will be presented as well as the main Cognitive Linguistics pragmatic models that uphold the proposal of a systematic methodology to capture the communicative intentions of the therapeutic pair. These models are Grice’s (1975) Theory of the Implicatures, the Costa’s (1984) Extended Model of Theory of the Implicatures and the Sperber’s& Wilson (1986, 1995) Relevance Theory. At the end of the article some conclusions are drawn regarding the importance of the development of interdisciplinary proposals and of the Interface Science for the advancement of the CBTs. The importance of the use of the pragmatic theories is also explained as a way of understanding the communicative intentions in the communicational act which go beyond the semantics of the statements and allows the implicit content present in psychotherapic dialogues.